2011
DOI: 10.1097/igc.0b013e31821872f4
|View full text |Cite
|
Sign up to set email alerts
|

Defining Prognostic Variables in Recurrent Endometrioid Endometrial Cancer

Abstract: Those patients with high-grade histology at the time of initial diagnosis manifest a decreased OS and RS, suggesting that the intrinsic biology of the tumor has the greatest prognostic importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…However, a few studies in the literature have attempted to distinguish between type of nodal involvement and what we consider to be the rN2 group is often classified as distant recurrence sites. 5,21,22,25 In our study, metastases represented the first pathway of recurrence and was found in 95 women (38.6%) with a similar distribution between isolated and multiple metastases. This rate is in complete agreement with that reported by Sohaid et al 12 who found that metastases occurred in 36% of recurrences and represented a major predictor factor for poor survival.…”
Section: Discussionsupporting
confidence: 62%
“…However, a few studies in the literature have attempted to distinguish between type of nodal involvement and what we consider to be the rN2 group is often classified as distant recurrence sites. 5,21,22,25 In our study, metastases represented the first pathway of recurrence and was found in 95 women (38.6%) with a similar distribution between isolated and multiple metastases. This rate is in complete agreement with that reported by Sohaid et al 12 who found that metastases occurred in 36% of recurrences and represented a major predictor factor for poor survival.…”
Section: Discussionsupporting
confidence: 62%
“…Overall after treatment 10-15% of patients will experience disease recurrence [4,5]. When recurrent disease is localized in the vagina, salvage radiation therapy or surgery are effective at disease control and complete response rates approach 80-90% with 3-year overall survival rates of 48-82% [5][6][7][8][9][10][11][12]. Pelvic recurrence and distant metastases have lower control rates after recurrence and shorter overall survival [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Various factors have been shown to be prognostic for survival and overall outcomes after recurrence of endometrial carcinoma including: vaginal recurrence compared to recurrences at other sites [5,9,10,[12][13][14], endometrioid histology [14,15], use of adjuvant radiation therapy [5,9,13,14], initial tumor grade [8,12,16], and age at time of recurrence [16]. Among the various prognostic factors analyzed, the time from hysterectomy to recurrence or the disease-free interval remains controversial with some studies suggest a prognostic significance of a shorter time to recurrence (TTR) [9,10,13,15,16], while others did not [7,12,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In women with EC, tumor recurrences tend to occur in the 2-to 3-year period after initial treatment (60% of relapses diagnosed within 2 years and 76% within 3 years). 2 Despite this, recurrences can occur more than 15 years after completion of treatment.…”
mentioning
confidence: 99%
“…5,6,14Y17 However, factors predictive of survival after recurrent early-stage disease have not been thoroughly delineated. Although useful, previous studies were hampered by some study limitations, for example, inclusion of nonendometrioid histological subtypes, 2 all stages, 5,8 or small study cohort. 9 The objective of this study was to investigate the prognostic significance of certain tumor and treatment factors and their impact on disease-specific survival (DSS) and overall survival (OS) in women with recurrent early-stage EC solely of endometrioid histology.…”
mentioning
confidence: 99%